One Fusion Among Many: Merging Bali, India, and the West through Modernism - Tenzer, Michael (Circuit)

(untitled) (Les Presses de l’Université de Montréal, 2011)
The relationship between world music traditions and modernist art music in the European tradition is often explored in composers’ musical fusions, but the motivations and aesthetics of such works often receive less notice than those grounded in post-modern (minimalist, popular music) approaches. In this essay the author asserts a particular relationship between rigorous modern composition technique and the highly rational patterning of Indonesian and Indian music, and follow this with analysis of Unstable Centre/Puser Belah (2003) a work composed for two simultaneous Balinese gamelan. The analysis demonstrates fusion at detailed levels of pattern and structure, but the article closes with a self-critical assessment of the venture.